Elemental magic. - Gilland, Joseph (Focal Press, 2012)
A guide to creating hand-drawn and digital effects includes step-by-step diagrams and explanations for the entire spectrum of animated effects, including liquids, fire, smoke, rippling water, and spiritual entities.